Criteria for selection in the portfolio of trading systems - K. E. Ladygin; V. A. Galanov (Путеводитель предпринимателя)
The article classified the criteria by which it is possible to carry out a targeted selection of existing variety of trading systems used in the creation of modern trading robots. Knowledge of this kind of classification allows to accelerate the processes of trading strategies research, which can be combined into a single unit, denoted by a portfolio of automated trading systems.